2012
DOI: 10.5402/2012/365438
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Application in Dental Cements

Abstract: Streptococcus mutans is the microorganism mostly responsible for initiation of tooth decay and also for the progression of an established lesion. Silver has been used for its antibacterial properties for many years, in different forms: ionised and elementary forms, as silver zeolites or as nanoparticles. The purpose of this study was to evaluate the antibacterial activity of three dental cements modified by nanosilver. Three cements were used: Sealapex, RelyX ARC, and Vitrebond. The cements were incorporated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 34 publications
2
28
0
3
Order By: Relevance
“…A recent study by Chladek et al found that incorporating AgNPs into dental composites could reduce the microbial colonization of lining materials, enhancing the antifungal efficiency [111]. Similarly, AgNPs incorporated into endodontic fillings displayed an increased antibacterial effect against Streptococcus milleri, S. aureus, and E. faecalis [112].…”
Section: Dentistrymentioning
confidence: 99%
“…A recent study by Chladek et al found that incorporating AgNPs into dental composites could reduce the microbial colonization of lining materials, enhancing the antifungal efficiency [111]. Similarly, AgNPs incorporated into endodontic fillings displayed an increased antibacterial effect against Streptococcus milleri, S. aureus, and E. faecalis [112].…”
Section: Dentistrymentioning
confidence: 99%
“…(i) Dental Material (Class I) Studies have shown that AgNP infused dental filling cements have remarkable bactericidal effects [81]. Adding AgNP to orthodontic adhesives has also demonstrated notable antimicrobial properties, which in turn prevents enamel demineralization without jeopardizing the physical attributes of the adhesive in the process [82].…”
Section: Silver Nanoparticles In Biomedical Devicesmentioning
confidence: 99%
“…Azimi et al (35) demonstrated that the greater antifungal effect of AgNPs on S. mutans and S. sanguis than Nigella sativa oil. The inhibitory effects of AgNPs on the growth of Gramnegative bacteria E. coli and Gram-positive bacteria S. aureus and S. mutans were confirmed (36,31). All of which appeared to be in agreement with our findings and other results reported about the antimicrobial activity of AgNPs.…”
Section: Discussionmentioning
confidence: 90%